Genetics of resistance to bean golden mosaic virus in Phaseolus vulgaris L. - Morales, Francisco José; Singh, Shree P. (1991)
The genetics of resistance to bean golden mosaic virus (BGMV) was studied in an 8×8 complete diallel cross of common bean, Phaseolus vulgaris L. The 28F1 hybrids, their reciprocals, and eight parents were artificially inoculated with BGMV under glasshouse conditions. Data were recorded and analyzed for foliar yellowing, plant dwarfing, flower abortion, and pod formation, using a randomized complete block design with two replications. General combining ability (GCA) mean squares were highly significant (P<0.01) and larger than values for specific combining ability for all traits. Reciprocal and maternal effects were nonsignificant. Cultivars Royal Red and Alubia Cerrillos possessed significant negative and positive GCA for all traits, respectively. Porrillo Sintetico also had negative GCA for all traits except plant dwarfing. None of the GCA effects were significant for Great Northern 31 and PVA 1111. Positive associations existed among all traits studied.